BIAK: Ruang Interaksi Sosial Antar Penyandang Disabilitas - Fabianus Selatang; Jenitriana Neonbasu (Jurnal Pelayanan Pastoral, 2020)
This research aims to describe the effect of BIAK implementation on social interaction between people with disabilities in Seruni Complex. This type of research is non-experimental research using a descriptive quantitative approach. The population in this study was 46 people with different types of limitations. The determination of samples using purposive sampling techniques, so the samples in this study were 10 children with disabilities classification of the deaf. The data was collected through an indirect closed questionnaire technique in which the questionnaire contained a list of statements about others and was filled in by respondents who knew about the person. Analyze data using spss software program version 16. The results showed that the hypothesis test using the t test analysis, obtained t count by 2,800, so that t count > t Table (2,800 > 1,812) which is statistically 49.5% Biak implementation affects social interaction between people with disabilities. This research illustrates that there is a positive and significant influence of BIAK implementation on social interaction between people with disabilities in Komplekss Seruni. In conclusion, through the implementation of BIAK, social interaction between people with disabilities will be better.